A Systematic Review of PjBL in Chemistry Education: Bridging Theory and Practice - Aslam, Shazia; Ikhsan, Jaslin; Ali, Salman; Ali, Safdar (Jurnal Inovasi Pendidikan IPA, 2025)
Project-based learning (PjBL) is an innovative educational approach that integrates real-world contexts to enhance student engagement and learning outcomes, particularly in chemistry education. This systematic review examines the effectiveness of PjBL in teaching organic compound separation techniques, a critical area in both academic and industrial applications. Based on a synthesis of 10 selected studies from the last five years, the review highlights the impact of PjBL on improving student engagement, conceptual understanding, and laboratory competencies. Students involved in PjBL activities showed greater motivation and deeper conceptual learning, particularly in mastering complex techniques such as chromatography and distillation. Furthermore, PjBL enhanced collaboration, critical thinking, and problem-solving through active participation in hands-on tasks. Despite these benefits, several challenges were identified, including limited resources, time constraints, and insufficient teacher training. This review offers strategic recommendations, including the development of low-cost resources and the expansion of professional development programs. Future research should investigate the long-term effects of PjBL on academic achievement and career readiness, especially within STEM education contexts